Youth exposure to in-vehicle second-hand smoke and their smoking behaviours: trends and associations in repeated national surveys (2006–2012). Issue 2 (17th September 2013) - Healey, Benjamin; Hoek, Janet; Wilson, Nick; Thomson, George; Taylor, Steve; Edwards, Richard
Abstract : Objective: To extend the limited international evidence on youth in-vehicle second-hand smoke (SHS) exposure by examining trends in New Zealand, a country with a national smoke-free goal and indoors smoke-free environment legislation. Methods: We tracked exposure rates and explored the associations between in-vehicle SHS exposure and smoking behaviours. In-home exposure was also examined for comparative purposes. Data were collected in annual surveys of over 25 000 year 10 school students (14–15-year olds) for a 7-year period (2006–2012). Questions covered smoking behaviour, exposure to smoking and demographics. Results: Youth SHS exposure rates in-vehicle and in-home trended down slightly over time (p<0.0001 for both) with 23% exposed in-vehicle in the previous week in 2012. However, marked inequalities in exposure between ethnic groups, and by school-based socioeconomic position, persisted. The strongest association with SHS exposure was parental smoking (eg, for both parents versus neither smoking in 2012: in-vehicle SHS exposure adjusted OR: 7.4; 95% CI: 6.5 to 8.4). After adjusting for seven other factors associated with initiation, logistic regression analyses revealed statistically significant associations of in-vehicle SHS exposure with susceptibility to initiation and smoking. Conclusions: The slow decline in SHS exposure in vehicles and the lack of progress in reducing relative inequalities is problematic. To accelerate progress, the New Zealand Government could follow the example of other jurisdictions and prohibit smoking in cars carrying children. Other major policy interventions, beside enhanced smoke-free environments, will also likely be required if New Zealand is to achieve its 2025 smoke-free nation goal.